2019
DOI: 10.25259/sni-44-2019
|View full text |Cite
|
Sign up to set email alerts
|

Transradial approach for endovascular diagnosis and treatment of ruptured cerebral aneurysms: A descriptive study

Abstract: Background: For cardiovascular procedures, the transradial approach has been documented to yield fewer complications than the femoral approach. It has become the approach of choice for diagnostic and therapeutic interventions involving the coronary arteries. However, few published data exist on using this approach for neuroendovascular procedures and we describe a series of ruptured cerebral aneurysms diagnosed and treated using the transradial approach. Methods: All patients scheduled for cerebral angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…[4] The procedure continues as described in previous articles on the diagnosis and treatment of cerebral aneurysms by the radial route. [3,4]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] The procedure continues as described in previous articles on the diagnosis and treatment of cerebral aneurysms by the radial route. [3,4]…”
Section: Methodsmentioning
confidence: 99%
“…The transradial approach has emerged as a neurointerventional option for the diagnosis and treatment of cerebral aneurysms. [3-6,9,10] Comparative studies of patients who underwent radial or femoral cardiac catheterization have shown that the transradial approach results in fewer complications at the puncture site, lower hospital costs, and greater comfort for patients. [1,7]…”
Section: Introductionmentioning
confidence: 99%
“…A 60-year-old woman presented to our unit with a subarachnoid hemorrhage: Hunt Hess 4, Fisher 4 ( Figure 1 ). The patient was intubated, then a right radial approach was used to occlude the aneurism using a technique described in previous publications [ 4 , 5 ].…”
Section: Case Reportmentioning
confidence: 99%
“…Furthermore, while transfemoral access has been the preferred approach during neurointerventional procedures for decades (6), recent studies have shown the promise of transradial access for the diagnosis and treatment of various cerebral pathologies with embolization, mechanical thrombectomy, microsurgical aneurysm clipping, stenting, and balloon occlusion tests (7)(8)(9). While studies of safety and efficacy of radial access are ongoing, a key and understudied aspect of this procedure is the feasibility of using current long guiding sheaths in this novel application across disease states.…”
Section: Introductionmentioning
confidence: 99%